Определение диэлектрических параметров изоляции трансформаторов тока при множественных измерениях в системах контроля под рабочим напряжением - Беляев, Виталий Константинович; Паненко, Елена Николаевна (НТУ "ХПИ", 2016)
Рассмотрены особенности методик обработки результатов множественных измерений тангенса угла диэлектрических потерь высоковольтной изоляции, основанных на методе сравнения. Проанализированы известные методики определения тангенса потерь с выделением отдельного эталонного объекта и без выделения такого эталона. Получены выражения для определения методических погрешностей. Проведено сравнение и показано, что применение методик обработки без выделения отдельного эталонного объекта может приводить к существенным сложностям в оценке результатов контроля изоляции. Предложены усовершенствования методик обработки, уменьшающие указанные погрешности методик и трудоемкость измерений.

Features of the data processing procedures of multiple measurements of the dielectric loss tangent of the high-voltage insulation, which are based on the comparison method, were considered. Three procedures were compared: the one procedure uses an assignment of a particular standard object for comparison, and two procedures don't use assignments of the special standard objects. Expressions of methodical errors of studied procedures were obtained. Analysis and calculations, which use the obtained expressions were made. Evaluations showed that an influence of a change of the tangent of dielectric loss of one from the monitoring objects on results of estimation of the tangents of other monitoring objects is the distinctive feature of the procedures without assignment of the standard object. Errors of these procedures more than errors of the traditional procedure, with assignment of the standard object. The study demonstrated that procedures without assignment of standard objects lead to difficultly predictable methodological errors, which hinder to estimate the actual value of the loss tangent and to estimate outcomes of the monitoring, by means comparing with allowable values. Moreover, the decrease of estimations of loss tangents of all objects, as a result of occurrence of at least one the object with strongly bad parameters, hides occurrence of other unsuccessful objects with smaller deviations and makes difficult recognition of such deviations at early stages. Improvements in processing techniques which reduce earlier specified errors and reduce the amount of measurements are proposed. The study results are useful in monitoring and diagnostic of basic insulation of current transformers or highvoltage bushings.
Determination of insulation parameters of current transformers at multiple measurements in monitoring systems under working voltage
Keywords: высоковольтная изоляция; диагностика; методика обработки; погрешность; тангенс угла диэлектрических потерь; трансформатор тока; high voltage insulation; diagnostics; data processing procedure; processing procedure error; dielectric loss tangent; current transformer